PERAN POLA ASUH PENGASUH PONDOK PESANTREN TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL SANTRI USIA 7-12 TAHUN DAN IMPLIKASINYA BAGI SISWA MI - Arifah Amani; Ariga Bahrodin (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The parenting pattern in every Islamic boarding school cannot be separated from the presence of a leader of the Islamic boarding school, namely a Kyai. Kyai is someone who has full authority and fully leads the implementation rules in the Islamic boarding school. Kyai is also a very important person in parenting, because in the hands of the Kyai will be determined the parenting pattern and the educational process that is carried out. The purpose of this study is to investigate in depth the relationship between the parenting pattern of Islamic boarding school caregivers and children's social-emotional development. By analyzing the specific facts and factors in parenting patterns that can influence the development of children's social-emotional development, this study aims to make a significant contribution to our understanding of how the family environment plays an important role in forming the basis for children's social-emotional development. Research results 1. The parenting pattern of caregivers is reflected as an authoritative parenting pattern that is contextualized with a religious and institutional approach typical of Islamic boarding schools. This parenting pattern is characterized by a balance between control and emotional closeness. 2. Implications of the parenting pattern of caregivers through a. application of authoritative parenting patterns b. discipline and emotional regulation c. affection and appreciation as the basis for positive emotions d. independence and self-identity e. instilling moral and social values f. emotional involvement of caregivers and responses to children g. evaluation and adaptation of parenting patterns.